Auditor Experience as Moderator on Audit Quality in creating Qualified Financial Statements - Sarwenda Biduri; Sigit Hermawan; Wiwit Hariyanto; Endra Wahyu Ningdia (AKRUAL: JURNAL AKUNTANSI, 2021)
This study aims to analyze the effect of the variable budget pressure, auditor independence, and professional care due on the audit quality variable moderated by the auditor's experience variable with the help of the SPSS application program. Data was collected through a questionnaire method with 43 respondents using convenience sampling technique to determine the respondents' responses to each variable. The analysis shows that time budget pressure and auditor independence have no partial effect on audit quality, while "due professional care" has partial effect on audit quality. Time budget pressure, auditor independence, and due professional care simultaneously affect auditor performance. Auditor experience is not a moderating variable, but a moderating predictor. Auditors are expected to improve audit quality by continuing to work independently and be responsible for the agreed/determined time. Future researchers are expected to be able to expand the scope of the research object so that it is expected to add variables that affect audit quality